Catlyst of Abolition: The Paraguayan War and Brazilian Demands for Emancipation, 1864-1870 - Wendorf, Joseph W. (My University, 2008)
This paper examines the issue of slavery in Brazil throughout the nineteenth century, highlighting the significance of the Paraguayan War on the legitimacy and acceptance of slave labor. What happened in six years of confrontation with neighboring Paraguay completely altered the make-up of Brazil’s social climate and political culture. Slaves responded to opportunities created by the war. They escaped from their owners to join the army, found refuge in quilombos, appealed to local authorities for freedom and better treatment, or simply fled to other provinces. Freed and enslaved blacks soon found that the war had created a strong sense of disillusionment within a large percentage of Brazil’s lower- and middle- classes and returning soldiers alike. Their confidence in the government’s politics and practices pertaining to the Paraguayan War had long vanished after witnessing the harsh recruitment practices and malicious treatment of soldiers. With the final emergence of a republican-minded movement opposed to Emperor Pedro II and the monarchial institution, emancipation legislation was finally pushed through in 1871 granting freedom to all children born of a slave mother and thus ending any potential viability for the institution’s dominant role in Brazilian society.
Keywords: Slavery--Brazil--History.; Slaves--Emancipation--Brazil.; Paraguayan War, 1865-1870.; Brazil--Social conditions--19th century.; Brazil--Politics and government--1822-1889.; Brazil--History--Empire, 1822-1889.